2012
DOI: 10.1248/cpb.60.674
|View full text |Cite
|
Sign up to set email alerts
|

Medicinal Flowers. XXXIII. Anti-hyperlipidemic and Anti-hyperglycemic Effects of Chakasaponins I–III and Structure of Chakasaponin IV from Flower Buds of Chinese Tea Plant (<i>Camellia sinensis</i>)

Abstract: Effects of principal saponins, chakasaponins I-III, from the flower buds of Camellia sinensis cultivated in Fujian province, China on plasma triglyceride (TG) and glucose levels in olive oil or sucrose-loaded mice were examined. Chakasaponins I-III at 50 and 100 mg/kg significantly inhibited increases in plasma TG and glucose levels. Furthermore, they prevented gastric emptying, suggesting that the former inhibitory effect is partly dependent on the inhibition of gastric emptying. In addition, the chemical str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
28
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 18 publications
(34 reference statements)
1
28
0
Order By: Relevance
“…[2][3][4][5][6] However, a full chemical analysis of the flowers from this plant has not yet been performed. In the course of our chemical and pharmacological studies on Hydrangea plants [2][3][4][5][6][7][8] and medicinal flowers, [9][10][11][12][13][14] we recently reported the isolation and structure elucidation of secoiridoid glycosides named hydrangeamines A and B with a pyridine ring from the flowers of H. macrophylla var. thunbergii cultivated in Nagano prefecture, Japan.…”
mentioning
confidence: 99%
“…[2][3][4][5][6] However, a full chemical analysis of the flowers from this plant has not yet been performed. In the course of our chemical and pharmacological studies on Hydrangea plants [2][3][4][5][6][7][8] and medicinal flowers, [9][10][11][12][13][14] we recently reported the isolation and structure elucidation of secoiridoid glycosides named hydrangeamines A and B with a pyridine ring from the flowers of H. macrophylla var. thunbergii cultivated in Nagano prefecture, Japan.…”
mentioning
confidence: 99%
“…of Fuijian Chaka also inhibited plasma TG elevation in olive oil-loaded mice and plasma glucose elevation in sucrose-loaded mice [12]. Chakasaponins I ( 11 )–IV ( 14 ) isolated from Fujian Chaka, and their chemical structures were determined [12, 16].…”
Section: Biofunctional Effects Of Fujian Chakamentioning
confidence: 99%
“…of Fuijian Chaka also inhibited plasma TG elevation in olive oil-loaded mice and plasma glucose elevation in sucrose-loaded mice [12]. Chakasaponins I ( 11 )–IV ( 14 ) isolated from Fujian Chaka, and their chemical structures were determined [12, 16]. In addition, chakasaponins V ( 15 ) and VI ( 16 ) together with floratheasaponins A ( 1 )–I ( 9 ), chakasaponins I ( 11 )–III ( 13 ), and assamsaponin E ( 25 ) were isolated from the dried flower buds of C. sinensis cultivated in Sichuan province of China (Sichuan Chaka) [22].…”
Section: Biofunctional Effects Of Fujian Chakamentioning
confidence: 99%
See 1 more Smart Citation
“…In the course of our studies on bioactive constituents from medicinal flower, [2][3][4][5][6] we previously reported the isolation and structure elucidation of acylated sucroses named prunoses I (11), II (12), and III (13) with inhibitory effects on platelet aggregation and aldose reductase and radical scavenging effect from the flower buds of Prunus (P.) mume Sieb. et Zucc.…”
mentioning
confidence: 99%